Preconception menstrual cycle disorder and antenatal depression: a cross-sectional study with prerecorded information - Natsu Sasaki; Hiroto Akiyama; Norito Kawakami; Daisuke Nishi (Taylor & Francis Group, 2022)
Objectives This study aimed to evaluate the association between pre-pregnancy menstrual cycle characteristics (i.e. cycle-length variability and cycle length) and antenatal depression. Methods This study retrieved the data from the baseline survey of the randomized controlled trial with pregnant women at 16-20 weeks gestation who used a pregnancy tracking app. The antenatal depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS) at 16-20 weeks gestation, and the cutoff point of 10/11 was adopted. Pre-conceptional menstrual cycle information was obtained via a prerecorded period tracking app. Cycle-length variability was defined as the average difference in the lengths between cycles, dichotomized into regular (≤6 days) and irregular (>6 days). Cycle length was coded as a categorical variable: <25 days, 25-26 days, 27-29 days (regular), 30-31 days, 32-33 days, and 34+ days. The associations of cycle disorders with EPDS scores were examined using regression analysis and a multiple logistic regression model adjusted for covariates. Results The total of 3473 participants were analyzed in this study. Irregular cycle variability (>6 days) was significantly associated with high EPDS scores (adjusted: standardized beta = 0.049, p = 0.003) and with high cutoff EPDS scores (over 11) (adjusted OR = 1.40 [1.02-1.94], p = 0.038) but not with cycle length. Conclusion Irregular menstrual cycle before pregnancy was associated with depression during pregnancy. The health of the menstrual cycle during preconception needs to be further explored to promote healthy maternal mental health.